Modified Boost Derived Hybrid Converter: Redemption Using FCM - Chauhan A.K.; Vakacharla V.R.; Reza M.M.; Raghuram M.; Singh S.K. (My University, 2025)
Boost-derived hybrid converter (BDHC) is a single-stage converter that produces both dc and ac output voltages. The operation of BDHC under continuous conduction mode is satisfactory. However, the nonzero discontinuous conduction mode (NZ-DCM) and standalone ac operation restrict the stable operation of the converter. To mitigate these limitations, modified BDHC (MBDHC) is proposed in this paper. The main idea behind these changes is to redeem NZ-DCM by forced continuous conduction mode (FCM). The adverse effect of NZ-DCM in a BDHC is analyzed in terms of ac output voltage total harmonic distortion, and dc output voltage ripple. This analysis is further extended for MBDHC to highlight the benefits of FCM. Moreover, for hybrid loads, the efficiency of MBDHC is compared with its counterpart BDHC and cascaded boost inverter. © 1972-2012 IEEE.